Antonio Miguel BERNAL, España, proyecto inacabado: costes/beneficios del Imperio. Marcial Pons. Madrid, 2005 - Dedien, Jean Pierre; Dobado, Rafael; Pérez Herrero, Pedro (Cuadernos de Historia Moderna, 2007)
Sin resumen